2019
DOI: 10.1186/s12893-019-0507-7
|View full text |Cite
|
Sign up to set email alerts
|

Omentopexy with Glubran®2 for reducing complications after laparoscopic sleeve gastrectomy: results of a randomized controlled study

Abstract: BackgroundGastric fistulas, bleeding, and strictures are commonly reported after laparoscopic sleeve gastrectomy (LSG), that increase morbidity and hospital stay and may put the patient’s life at risk. We report our prospective evaluation of application of synthetic sealant, a modified cyanoacrylate (Glubran®2), on suture rime, associated with omentopexy, to identify results on LSG-related complications.MethodsPatients were enrolled for LSG by two Bariatric Centers, with high-level activity volume. Intraoperat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 28 publications
0
19
0
Order By: Relevance
“…Heterogeneity between studies was significantly high (l2 92%). We observed that there is a noticeable difference in time range: Pilone et al reported LOS in days (4.5 versus 5.8), but Hassan et al reported in hours (32+/−9 versus 40+/−8) [13,16]. The difference may depend on the method of calculating the length of stay in the hospital and on well-developed outpatient care in accordance with the ERAS protocol [24,25].…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Heterogeneity between studies was significantly high (l2 92%). We observed that there is a noticeable difference in time range: Pilone et al reported LOS in days (4.5 versus 5.8), but Hassan et al reported in hours (32+/−9 versus 40+/−8) [13,16]. The difference may depend on the method of calculating the length of stay in the hospital and on well-developed outpatient care in accordance with the ERAS protocol [24,25].…”
Section: Discussionmentioning
confidence: 78%
“…Sharma et al, in their technique, placed 2-4 sutures at the site proximal to incisura and one suture at the most distal end of staple line [14]. Pilone et al, after formation of the sleeve, applied a layer of the synthetic sealant on all rime sutures and cover it by an omentum flap [13]. In Batman et al, omentopexy is performed by suturing the omentum back to the greater curvature with V-Loc sutures along the entire staple line [17].…”
Section: Discussionmentioning
confidence: 99%
“…Omentopexy during Laparoscopic sleeve gastrectomy, is one method amongst others that have been hypothesized to reduce the various complications Laparoscopic sleeve gastrectomy has been associated with, for example, gastric leaks, gastric obstruction due to strictures or rotation, and gastrointestinal complaints. A consensus has not been reached currently regarding this hypothesis, as current studies show mixed results, some favorable, while others no significant outcome (4) . This prospective randomized controlled clinical trial study was conducted in the Zagazig University hospital including 30 patients with morbid obesity who were admitted to the General Surgery Department, for intervention surgery with laparoscopic sleeve Gastrectomy during the period from July 2020 to August 2021 to assess the safety & feasibility of the omentopexy technique in Laparoscopic sleeve gastrectomy.…”
Section: Discussionmentioning
confidence: 91%
“…In fact, the longer the chain of the cyanoacrylate is, the less cytotoxic adhesion [3]. The use of Glubran®2 has been expanded as a duroplasty glue [2], Omentopexy and abdominal hernia fixation [6], bronchopleural fistula sealing [7], for decreasing alveolar air leak in thoracic surgery [8] and brain tumors embolization. [4].…”
Section: Discussionmentioning
confidence: 99%